Complete mitochondrial genome of Hippophae tibetana: insights into adaptation to high-altitude environments - Zeng, Zhefei; Zhang, Zhengyan; Tso, Norzin; Zhang, Shutong; Chen, Yan; Shu, Qi; Li, Junru; Liang, Ziyi; Wang, Ruoqiu; Wang, Junwei; Qiong, La (Frontiers in Plant Science, 2024)
Hippophae tibetana, belonging to the Elaeagnaceae family, is an endemic plant species of the Qinghai-Tibet Plateau, valued for its remarkable ecological restoration capabilities, as well as medicinal and edible properties. Despite being acknowledged as a useful species, its mitochondrial genome data and those of other species of the Elaeagnaceae family are lacking to date. In this study, we, for the first time, successfully assembled the mitochondrial genome of H. tibetana, which is 464,208 bp long and comprises 31 tRNA genes, 3 rRNA genes, 37 protein-coding genes, and 3 pseudogenes. Analysis of the genome revealed a high copy number of the trnM-CAT gene and a high prevalence of repetitive sequences, both of which likely contribute to genome rearrangement and adaptive evolution. Through nucleotide diversity and codon usage bias analyses, we identified specific genes that are crucial for adaptation to high-altitude conditions. Notably, genes such as atp6, ccmB, nad4L, and nad7 exhibited signs of positive selection, indicating the presence of unique adaptive traits for survival in extreme environments. Phylogenetic analysis confirmed the close relationship between the Elaeagnaceae family and other related families, whereas intergenomic sequence transfer analysis revealed a substantial presence of homologous fragments among the mitochondrial, chloroplast, and whole genomes, which may be linked to the high-altitude adaptation mechanisms of H. tibetana. The findings of this study not only enrich our knowledge of H. tibetana molecular biology but also advance our understanding of the adaptive evolution of plants on the Qinghai-Tibet Plateau. This study provides a solid scientific foundation for the 2 molecular breeding, conservation, and utilization of H. tibetana genetic resources.